Ubuntu Linux Server Security Analysis and Simulation With Port Knocking & Iptable - Onno Widodo Purbo (Institute of Computer Science, 2019)
Computer network security is very important to maintain the confidentiality of data and information contained on the server. This data and information is only intended for administrators and users who have the right to access it through the service port. Leaving an important port open is a fatal mistake that can result in an attack on the server. The existence of Linux as an operating system kernel developed with a copyright or opensource model, computer networks using Linux servers are able to manage all internet services, including routers, database servers, proxy servers and FTP servers, in addition to the distributions. also easy to find in the market. One of them is ubuntu, ubuntu is one of the distributions that has been used by many people because Ubuntu has a user-friendly interface and many developers and is supported by a very large community. The method used in this study is the method of observation, interview and design of the Linux Ubuntu iptables operating system security, and the results of this study explain that the use of Iptables configuration on the Ubuntu Linux operating system can be done on a LAN and Wifi cable connection, as long as all clients are on the same class then the Iptables configuration can block client access to the server and can be done the other way around, namely blocking server access to the client. By using the accept setting, this system can also reject certain IP addresses or ports, in addition to accepting other connections. If you want to reject all connections and want to specify what connections you want to do manually, then you have to change the default setting from chain to drop. This method can only be useful for servers that have sensitive information, and only use the same IP address to connect to that server.